1999
DOI: 10.1002/(sici)1099-1441(199906)6:2<101::aid-kpm53>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The process of knowledge management within organizations: a critical assessment of both theory and practice

Abstract: This article critically assesses the current understanding of the theory and practice of the emerging field of Knowledge Management (KM), so that it can be more beneficially applied to organizations and those who work in them. More specifically the article discusses the emergent nature of KM, presents a short critical assessment of the literature on KM models, gives the results of primary research to assess the current state of KM theory and practice in organizations, and develops a model based on the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…A particular interpretativist KM model emphasize on the construction of knowledge, inside company, through an exchange social process in which knowledge is consecrated within their own company structures (Demarest, 1997). Once it has been incorpored to the organization, the knowledge it is disseminated through social processes (Demarest, 1997;McAdams & Mc Creedy, 1999, 1999a. This fact of emerging is a similar practice to the interpretativist work about KM of Orlikowski (2002), who presents knowledge as "emergent from actions located and occurring that company members commit themselves to perform".…”
Section: The Interpretativist Perspectivementioning
confidence: 99%
“…A particular interpretativist KM model emphasize on the construction of knowledge, inside company, through an exchange social process in which knowledge is consecrated within their own company structures (Demarest, 1997). Once it has been incorpored to the organization, the knowledge it is disseminated through social processes (Demarest, 1997;McAdams & Mc Creedy, 1999, 1999a. This fact of emerging is a similar practice to the interpretativist work about KM of Orlikowski (2002), who presents knowledge as "emergent from actions located and occurring that company members commit themselves to perform".…”
Section: The Interpretativist Perspectivementioning
confidence: 99%
“…Previous studies (McAdam & McCreedy, 1999;Moffett et al, , 2003 and current findings have shown that the MeCTIP model can be effectively used to represent constituent factors and components of KM.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from initial, exploratory research uncovered a number of key factors relating to KM McAdam & McCreedy, 1999). Application of these factors enabled a prescriptive, conceptual model of KM to be postulated.…”
Section: The Mectip Knowledge Management Modelmentioning
confidence: 99%
“…The terms knowledge transfer (Garvin, 1993;Gupta & Govindarajan, 2000a, 2000b, knowledge dissemination (Demarest, 1997;McAdam & McCreedy, 1999), knowledge flows (Gupta & Govindarajan, 2000b), and knowledge distribution (Huber, 1991) appear to be used interchangeably in the literature to describe the process of knowledge transfer. The literature identifies that knowledge transfer is a dynamic process between the individual or group and the organization's knowledge stocks.…”
Section: Understanding Knowledge Transfer (Kt)mentioning
confidence: 99%